Diagnostic features of representatives of Thymus sect. Serpyllum and T. sect. Marginati (Lamiaceae) and guidance for their herborization - Начичко, В. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The paper contains characteristics of morphological features that are traditionally recognized as "reliable" in the systematics of most critical sections in the genus Thymus L. (Lamiaceae): T. sect. Serpyllum (Mill.) Duby and T. sect. Marginati (A. Kern.) A. Kern. The taxonomic significance of these characters has been analyzed in the light of modern taxonomic concepts and the complex of unambiguous features has been selected. The features of shoot system organization and types of life forms are characterized as important diagnostic criteria, which are often ignored by botanists-taxonomists. The complex of diagnostic characters of Thymus representatives in the flora of Ukraine is provided and the guidance for herborization of thyme is proposed.